Designing and assessing solar energy neighborhoods from visual impact. (August 2021) - Florio, Pietro; Peronato, Giuseppe; Perera, A.T.D.; Di Blasi, Anthony; Poon, Kin Ho; Kämpf, Jérôme H.
Highlights: A Building Integrated PhotoVoltaics–BIPV design & assessment platform is presented. Simulations include façades, shading from vegetation and detailed roof-shapes. A visual impact assessment method is linked with microgrid feasibility & viability. Flexible module-scale vector data at hourly timestep is generated. Results indicate 32 % coverage of space heating energy from visually-acceptable PV. Abstract: The optimal diffusion of Building Integrated PhotoVoltaics (BIPV) in cities requires diligent planning to arrange temporal and spatial distribution of energy, while preserving the aesthetics of city landscapes. Benefitting from an increasing quality of 3D models of cities, a comprehensive methodology to estimate potential energy generation from visually-acceptable PV, energy use from buildings, and economically viable micro-grid operation is proposed, by combining validated dynamic energy simulation tools into an open-source computational platform. The platform intends to be useful for urban planners and officials in charge of planning a large-scale BIPV installation into an existing neighborhood: simulations are carried out at the city scale, inclusive of façade potential, shading from vegetation and detailed roof shapes with super-structures. Social acceptability is investigated through a novel visual impact assessment methodology and grid integration solutions are analyzed with reference to their associated costs. Under a conservative scenario, a median of 10 kW hAC-electricity / m 2 heated floor area per year is available from BIPV production in Geneva (Switzerland), covering 32 % electricity demand for space heating from heat pumps, or, alternatively, almost 10 times the one for space cooling. Visual impact has demonstrated not to be concurrent to grid integration constraints at the current stage, but rather to contribute to filtering building envelope surface and avoid grid curtailment of excess electricity. In the near future, with an increased grid efficiency, visual impact is expected to become a crucial criterion to limit the integration extent.